METHODS AND APPROACHES OF TRANSLATING AND ADAPTING ADVERTISING MESSAGES - Sherimbetova Meruert Alievna; Dilnoza Aliddinova Ramatullakyzy; Abdikamal Assylzat Sagyngazykyzy; Tangirkulova Asema Dinmukhamedkyzy (Foundations and Trends in Modern Learning, 2025)
Advertising has become an essential element of the consumer’s life, reflecting the society over the previous fifty years. The phenomenon of advertising is present in every commercial system. Advertising attempts to change the consumer’s perception of reality by presenting a different picture of the promoted product and implying that it is necessary. Advertising creators themselves construct a system by giving marketed products certain values. Thus, the promoted product gains the position of a mediator in men’s social interactions, and advertising itself turns into a sort of social lighthouse